Autoionizing Rydberg Series in the Photoionization of the 4s24p2 (3P1) and 4s24p2 (1D2) Excited States of the Br3+ Ion (Письма в ЭЧАЯ, 2024)
The photoionization of the 4s24p2 (3P1) and 4s24p2 (1D2) metastable states of the Br3+ ion is studied, and the autoionization spectra of the 4s4p2 (3P1)np and 4s4p2 (1D2)np Rydberg resonance series are investigated theoretically using the screening constant per unit nuclear charge (SCUNC) method. The resonance energies, quantum defects and effective charges of 8 autoionization resonance series originating respectively from the 4s24p2 (3P1) and 4s24p2 (1D2) mestastable states of the Br3+ ion due to 4s ® np transitions converging to the 4s4p2 (4P3/2) and 4s4p2 (2D5/2) series limits in Br4+ are reported up to n = 40. The analysis of the present results has been carried out within the framework of standard quantum defect theory and the SCUNC procedure by calculating the effective nuclear charge. Our theoretical resonance energies are compared with recent experimental measurements by Macaluso et al. (J. Phys. B At. Mol. Opt. Phys. 52:145002, 2019) for n = 5 – 17. Comparisons show excellent agreement between calculated resonance energies and experimental data. The very good agreement between theoretical and experimental data reinforces confidence in our new extrapolated theoretical data for n = 17 – 40 for astrophysical applications, in particular the determination of Br abundances in astronomical objects which depend strongly on the availability of accurate and weak atomic data.